Assessing the Impact of Corporate Governance on Performance: A Case Study of Agricultural Co-operatives in Mato Grosso do Sul, Brazil - Américo , Jean Carlos da Silva; Caleman , Silvia Morales de queiroz; Costa, Davi Rogerio de Moura; Campeão , Patrícia (Journal of Interdisciplinary Knowledge, 2019)
This study focuses on examining the relationship between corporate governance practices and the performance of agricultural co-operatives in Mato Grosso do Sul, Brazil. The primary objective is to address agency conflicts within co-operatives by investigating the extent to which corporate governance practices align the interests of co-operatives and their members. The research approach involved a document analysis using the bylaws and meeting minutes of 21 co-operatives, totaling 84 documents. The assessment of corporate governance levels was based on a comparison with the 40 recommendations proposed by the Brazilian Co-operatives Organization (OCB, 2016), categorized into five major areas. The study is grounded in agency theory, particularly focusing on monitoring and incentives as key aspects. The findings reveal that the majority of recommended governance practices are concentrated in the "management board" area, while the co-operatives' most adopted practices are related to the "members and general assembly" dimension, which primarily involves monitoring efforts. However, when considering the full set of OCB's recommendations, only two were fully implemented by the co-operatives. These results indicate a low level of corporate governance in agricultural co-operatives in Mato Grosso do Sul.